Benefit of Negative Pressure Drain Within Surgical Wound After Cytoreductive Surgery for Ovarian Cancer. Issue 1 (1st January 2015) - Kim, Se Ik; Lim, Myong Cheol; Bae, Hyo Sook; Shin, Se Ra; Seo, Sang-Soo; Kang, Sokbom; Park, Sang-Yoon
Abstract : Objective: The objective of this study was to investigate the efficacy of subcutaneous negative-pressure wound drains on wound healing after cytoreductive surgery for ovarian cancer. Methods: A retrospective study was performed on patients who underwent cytoreductive surgery for epithelial ovarian cancer, between 2012 and 2013. The patients were divided into 2 groups, according to using (n = 163) and not using (n = 37) of subcutaneous wound drains, and wound outcomes were analyzed. Results: Patients' characteristics were not statistically different, except for the prolonged operative time in patients with wound drains (median, 395 vs 240 minutes; P = 0.001). A lower rate of wound infection (12.9% vs 27.0%; P = 0.032) was observed in the drain group. In the multivariate analysis, placement of subcutaneous wound drain was an independent prognostic factor for reducing wound complications: disruption (odds ratio [OR], 0.367; 95% confidence interval [CI], 0.145–0.929; P = 0.034) and wound infection (OR, 0.198; 95% CI, 0.068–0.582; P = 0.003). Bowel surgery at the time of cytoreductive surgery and prolonged operative time (≥360 minutes) were also associated with higher rates of disruption (OR, 2.845; 95% CI, 1.111–7.289; P = 0.029) and wound infection (OR, 4.212; 95% CI, 1.273–13.935; P = 0.019), respectively. Conclusions: Installation of subcutaneous negative-pressure wound drain is an effective method to achieve clearer wound healing and less wound complications after cytoreductive surgery for ovarian cancer.